Impostor syndrome, associated factors and impact on well-being across medical undergraduates and postgraduate medical professionals: a scoping review - Qian Hui Chew; Kang Sim; Shi Min Chua; Isac Yih Kiat Tan; Matthias Enrui Thummachai (BMJ Open, 2025)
Objectives Impostor syndrome (IS) is a psychological state whereby individuals doubt their abilities despite evidence of competence. Though IS has been studied in specific medical groups, no review to date compares findings across groups. This study aimed to: (1) determine the range of IS rates among medical undergraduates versus postgraduates and (2) examine associated factors across both groups.Design This scoping review used the Joanna Briggs Institute methodology for scoping reviews, using a five-step framework.Data sources PubMed, Scopus and PsycINFO databases were searched from inception until September 2024.Eligibility criteria Studies were included if they were (1) empirical studies with a defined IS rating scale, (2) involving medical undergraduates, residents or clinicians and (3) published in English.Data extraction and synthesis Three independent reviewers used standardised methods to screen and review selected studies, and extract key variables.Results 54 studies (77.8% from the West) were included. There was equal study distribution between undergraduates (46.3%, 25 studies) and postgraduates (46.3%, 25 studies), with the rest covering both groups. IS prevalence was substantial across all groups when assessed using the Clance Impostor Phenomenon Scale, ranging from 30.6% to 75.9% among undergraduates, 33.0% to 75.0% among residents and 23.5% to 50.0% among faculty and clinicians. In undergraduates, IS was associated with learning breaks, transition periods and poor academic performance. Among postgraduates, IS was correlated with younger age, junior ranking, fewer work years, inadequate faculty support or self-perceived poor clinical and teaching skills. Additionally, IS affected physical and psychological well-being (stress, anxiety, depression, burnout) and was associated with sociodemographic factors (single status, females), personality (neuroticism, perfectionistic traits, with conscientiousness, agreeableness and extraversion as protective) and interpersonal issues (conflicts, poor sense of belonging).Conclusions Given the high IS prevalence and associations with specific factors, practical measures are recommended to address IS and optimise learning and care for medical undergraduates and professionals.